Value At Risk (VAR) Analysis using Historical and Monte Carlo Methods in Stock Prices of Bank CIMB Niaga, BSI, BJB, Bank Mega, and Bank Bukopin - Helena, Putri Zahra; Puspitasari, Laras Dwi (International Journal of Global Operations Research, 2024)
In daily life and business, risk is unavoidable. Therefore, various ways can be applied to predict and overcome risks. One type of risk that needs to be anticipated especially in the business world is investment risk. Thus, Value at Risk (VaR) is an important tool to predict and anticipate investment risk. This study aims to determine the results of the Value at Risk (VaR) value in the bank sub-sector stock price using the historical simulation method and Monte Carlo simulation for the period 2020-2023. The data used is secondary data sourced from www.yahoo.finance.com which are companies whose stocks are listed on the Indonesia Stock Exchange (IDX) and included in the Indonesia Stock Exchange (IDX). Sampling was carried out by taking 5 bank companies, namely Bank Umum Koperasi Indonesia (BBKB), Bank Pembangunan Daerah Jawa Barat dan Banten (BJBR), Bank MEGA (MEGA), Bank Syariah Indonesia (BRIS), dan Bank CIMB Niaga (BNGA). From the results of the Value at Risk (VaR) value analysis using the historical simulation method and the Monte Carlo simulation method, it is obtained that the company that has the highest VaR risk level is Bank Syariah Indonesia (BRIS).